Maxillary distraction osteogenesis in cleft lip and palate patients using rigid external distractor. A review of the literature - Leiva-Villagra, Noemí (2019)
The cleft lip and palate is the most common congenital malformation among craniofacial anomalies and causes a series of functional, physiological, aesthetic and social alterations. One commonly characteristic associated with these patients is a severe maxillary hypoplasia as a result of the great resistance opposed by scar lip and palate tissue from a primary surgery. Traditionally, the suggested treatment has been conventional orthognathic surgery at the end of skeletal maturity. However, this approach has revealed certain limitations. Distraction osteogenesis using a rigid external distractor has shown to be a good alternative for these patients’ treatment, since it allows the gradual distraction of the maxilla and the associated tissues, thereby improving the short and long term results. A review of the available literature was performed to describe the maxillary distraction osteogenesis treatment scope using a rigid external distractor in cleft lip and palate patients with severe maxillary hypoplasia. It was concluded that maxillary distraction osteogenesis using a rigid external distractor is an effective, reliable and relatively stable procedure, with minimal associated complications. This could be a better alternative compared to conventional surgery for patients’ care having severe maxillary hypoplasia.